The temporal and spatial evolution law of seepage parameters in the filter based on the CFD-DEM coupled flow-solid approach - Song Jingyu; Dang Faning; Gao Jun; Zhu Wuwei; Yao Yi (Scientific Reports)
Abstract Filters are critical components of hydraulic structures such as earth-rock dams and tailings dams, functioning to prevent soil particle loss and control phreatic levels. Clogging failure in filters can severely compromise the seepage stability of dam slopes. This study simulates the clogging process using a CFD-DEM fluid–solid coupling method, focusing on three key factors: sediment particle size, fine particle concentration in muddy water, and seepage pressure. The spatiotemporal evolution of void ratio, hydraulic conductivity, and dry density during clogging is systematically investigated. Key findings include: (1) Surface clogging occurs when the particle size ratio Ra (filter-to-sediment diameter ratio) is less than 2.2, while particle penetration dominates when Ra exceeds 8.8. Internal clogging emerges at intermediate Ra values (2.2–8.8), with numerical results showing strong agreement with empirical criteria and pore network modeling (PNM). (2) Higher Ra values enhance particle penetration, whereas lower values promote clogging. Increased sediment concentration accelerates clogging stabilization, while fluid pressure gradients exhibit negligible influence on clogging patterns. (3) Under internal clogging, the void ratio follows an exponential decay pattern over time and depth. These findings provide theoretical and technical support for optimizing filter design and construction in geotechnical engineering.